The Design of Government. - Holmes, Neville (Computer (00189162), 2009)
The article presents the author's thoughts regarding the similarities between computer operating systems and government. The applicability of the skills of computing professionals to the proper design and implementation of systems of government is noted, mentioning that governments can be seen as systems which are characterized as possessing a high priority for reform. The need for technological competence in the highest levels of government is also noted, mentioning that governments are completely dependent on digital technology but are largely ineffective in implementing sizable digital projects.